In Search of His Majesty the King’s Underlying Concepts in Royally-Initiated Urban, Community and Architecture Development - Horayangkura, Vimolsiddhi; Pimonsathean, Yongtanit; Weesakul, Uruya; Lertpocasombut, Krittiya; Romratanapun, Worawut; Wongsawatgul, Eakaboon; Klinmalai, Siwaporn (Journal of Architectural/Planning Research and Studies (JARS), 2018)
King Bhumibol Adulyadej has been paid tribute to and presented with many international awards as the world’s “Development King.” Throughout 60 years of His Majesty’s reign, there have been over 3,000 royally-initiated projects for country development and improving the livelihood of his subjects. This research is intended to investigate His Majesty’s concepts in royally-initiated urban, community and architecture development, especially among those projects that are vital and beneficial to social and national development. It covers royally-initiated projects in urban development and improving the quality of life regarding traffic and transportation, flood mitigation, improvement of water quality, the provision of open spaces for urban areas, royally-initiated projects in self-reliant community development, community development through knowledge management, community development in enhancing spiritual and social cohesion, including royally-initiated projects in royal architecture and religious architecture development. Applicability analyses focus on the potential for future application in royally-initiated development models as well as on the legislative dimension. In parallel to examining the accomplishments and constraints of selected projects, comprehensive analyses are undertaken concerning concepts and theories/principles related to royal initiatives, His Majesty’s roles and concepts, royal statements and guidance, activities, etc. To provide a sufficient basis for concept investigation, relevant information was collected from documentary resources, physical surveys and structured interviews of key informants. Through systematic analyses of the arrays of concepts among various urban, community and architecture development initiatives, underlying development concepts, which are substantially philosophy/principles, have been emerged. Further integration of the proposed significant underlying concepts reveals a “sufficiency development” approach.